2011
DOI: 10.1007/s12149-011-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus evaluation for determining the chromosomal breakages after radionuclide synovectomy in patients with hemophilia

Abstract: Radioisotope synovectomy (RS) seems to be a safe procedure not causing a significant genotoxic effect on hemophilic patients, however, further studies including larger series of patients are needed to better understand the effects of RS on patients' health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Although, acute lymphoblastic leukemia (ALL) was reported in a child within the following year after RS (10) , the correlation was not strong and no increase in cancer incidence was shown in studies with large series that have been made to search for any possible relationship between RS and development of malignancies (11,12) . Theoretically RS might have genotoxic effect as a result of extraarticular leakage of radioactivity and whole body irradiation, but researches made concerning this potential adverse effect showed that RS does not induce the genotoxic effects on the peripheral blood lymphocytes in the paediatric population (13)(14)(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
“…Although, acute lymphoblastic leukemia (ALL) was reported in a child within the following year after RS (10) , the correlation was not strong and no increase in cancer incidence was shown in studies with large series that have been made to search for any possible relationship between RS and development of malignancies (11,12) . Theoretically RS might have genotoxic effect as a result of extraarticular leakage of radioactivity and whole body irradiation, but researches made concerning this potential adverse effect showed that RS does not induce the genotoxic effects on the peripheral blood lymphocytes in the paediatric population (13)(14)(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
“…Radiosynoviorthesis using an intraarticular injection of beta-emitting radiocolloids is a local treatment in patients suffering from inflammatory joint disease. Depending on the joint's size, three radiocolloids with different physical properties are used: [ 90 Y]yttrium citrate for the treatment of knee joints only, [ 186 Re]rhenium sulfide for mid-sized joints, and [ 169 Er]erbium citrate for small joints. The current official approvals and marketing authorizations in European countries are given in Table 2.…”
Section: Legislative Aspects and Approvals Throughout Europementioning
confidence: 99%
“…matory rheumatic disorders, in particular rheumatoid arthritis and in hemophilic arthropathy. • [ 186 Re]rhenium sulfide is indicated for the treatment of rheumatoid mono-or oligoarthritis involving mediumsized joints, including rheumatoid arthritis, hemophilic arthropathy, and chronic arthropathy associated with articular chondrocalcinosis. • [ 169 Er]erbium citrate is indicated for the treatment of rheumatoid mono-or oligoarthritis of small joints of hands and feet following the failure of intraarticular corticosteroid therapy or when the latter is contraindicated.…”
Section: Indications Documented In the Corporate Core Data Sheets (Ccds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the chromosomal changes after RS, several authors have shown that genotoxic radiation doses delivered to the peripheral lymphocytes are not statistically significant (17,18,19,20,21). However, transient increase in micronuclei of peripheral lymphocytes may be expected soon after Y-90 therapy which disappeared at 90 th .…”
Section: Introductionmentioning
confidence: 99%